2021
DOI: 10.1017/s0022215121000554
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory management of common ENT emergencies – what's the evidence?

Abstract: Objectives The global pandemic of coronavirus disease 2019 has necessitated changes to ‘usual’ ways of practice in otolaryngology, with a view towards out-patient or ambulatory management of appropriate conditions. This paper reviews the available evidence for out-patient management of three of the most common causes for emergency referral to the otolaryngology team: tonsillitis, peri-tonsillar abscess and epistaxis. Methods A literature review was performed, searching all available onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…5 Other studies reported the most common types of inpatient and outpatient otolaryngology consultations during the initial COVID-19 surge, and the methods of management with important safety considerations. 6,7 Despite the flurry of useful information on practice patterns during the first surge of the pandemic, there is no literature to date examining the lasting effect on otolaryngology practice as the healthcare system navigates to a new steady state. Measuring practice patterns is critical to continue to uphold our clinical and academic mission.…”
Section: Smentioning
confidence: 99%
See 1 more Smart Citation
“…5 Other studies reported the most common types of inpatient and outpatient otolaryngology consultations during the initial COVID-19 surge, and the methods of management with important safety considerations. 6,7 Despite the flurry of useful information on practice patterns during the first surge of the pandemic, there is no literature to date examining the lasting effect on otolaryngology practice as the healthcare system navigates to a new steady state. Measuring practice patterns is critical to continue to uphold our clinical and academic mission.…”
Section: Smentioning
confidence: 99%
“…5 Other studies reported the most common types of inpatient and outpatient otolaryngology consultations during the initial COVID-19 surge, and the methods of management with important safety considerations. 6,7…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Building on this, some have proposed standardized clinical care pathways for managing epistaxis while minimizing transfers, admissions, and ENT consults. [10][11][12] However, no studies yet have characterized the details of ENT consults for epistaxis in the ED. Thus, this study aims to analyze ED utilization and management for patients with epistaxis.…”
Section: Introductionmentioning
confidence: 99%